(Post-)Colonial Shakespeares: Macbeth in South Africa - Kholeif, Mahmoud T (AUC Knowledge Fountain, 2025)
The history of Shakespeare in South Africa is that of an often contested cultural battleground, with meanings fought over across a colonial boundary. In Chapter One, we examine some of the many cultural intersections between Shakespeare and South African rewriters. In the process, we can see how Shakespeare came to the region as a tool for colonial domination, but would eventually be used to rebuke the colonial narrative that was conservatively ascribed to him. He was used to enforce racial and political hierarchies, particularly through missionary education and institutions like the “Kaffir Institution.” The anxieties surrounding the ‘overproduction’ of Western-educated Black South Africans are examined through Homi Bhabha’s theory of colonial mimicry. Shakespeare’s dual role as both a tool of colonial control and a resource for anti-colonial resistance is a central point of focus for this thesis. By following the journey of Shakespeare through South Africa’s history, we can see how Black South African figures appropriated Shakespeare. Famed Setswana translator Solomon Tshekisho Plaatje even gave Shakespeare his Setswana name: “William Tsikinya-Chaka.” The second chapter of this thesis looks at Welcome Msomi’s uMabatha (1970), a Zulu adaptation of Macbeth. It argues that the play systematically flattens Zulu cultural forms to render them recognizable in a Shakespearean framework by stripping them of complexity. Though celebrated internationally as an “authentic” African Shakespeare, the play often caters to the Western view, giving credence to colonial stereotypes and minimizing the trauma of colonization. In the third and final chapter, we examine Pieter-Dirk Uys’ tragedy turned to farce MacBeki (2009) to reveal how the post-apartheid ruling elite mimic colonial and apartheid-era power structures. Uys’ adaptation transforms Shakespearean tragedy into farce, in the process highlighting the ongoing corruption of the ANC elite and disillusionment in their administration. The thesis as a whole shows that Shakespeare’s role in the South African cultural landscape has been that of a palimpsest, that is constantly reinscribed and reinterpreted to suit warring political agendas, emphasizing the ongoing negotiation of cultural identity and power.